Negotiating the Sacred and the Profane: The Kase Nae Tiang Alif Ritual of the Makeang People - Arlinah Arlinah; Safrudin Abd Rahman; Andi Sumar Karman (ETNOSIA : Jurnal Etnografi Indonesia, 2025)
Studies on local Islam in Indonesia have predominantly focused on Java and other major islands, leaving limited attention to the dynamics of Islamic practice in Eastern Indonesia. This article deals with a religious ritual of Makeang community by examining the Kase Nae Tiang Alif ritual as an expression of syncretic religiosity. The ritual, which is part of a mosque construction procession, merges sacred elements—such as prayers led by a hakim syara (Islamic judge)—with profane performances like the ronggeng togal dance. This ethnographic study was conducted in Ngofabobawa Village, Malifut District, North Maluku Province, between 2016 and 2019, employing participant observation and in-depth interviews with 23 informants of diverse backgrounds. The research findings show that the Kase Nae Tiang Alif ritual reflects the community’s negotiation between Islamic values, local cosmology, and ecological relationships. It serves not only as a religious act, but it also as a mechanism for communal solidarity and cultural continuity. The sacralization of the Tiang Alif (sacred pillar) demonstrates that local religiosity is rooted in symbolic practices that merge the divine and the material worlds. It is argued in this article that the ritual represents a space of negotiation between sacred and profane domains in the formation of local Islamic identity. This negotiation occurs through community participation, sensory expressions, and symbolic performances.